DEVELOPMENT STRATEGIES OF THE RUSSIAN TOURIST-RECREATIONAL COMPLEX - N. Korolev (Вестник университета, 2018)
The main tasks facing the tourist and recreational complex of Russia with a view to making it a highly profitable branch of the national economy of Russia were revealed: developing the infrastructure component of the Russian tourist complex, improving the quality of hotel and tourist services, and promoting Russia as a tourist center on the world tourism market. The example of a number of tourist and recreational clusters shows what has been done to date through the use of a program-targeted method that involves the use of federal budget funds, the budgets of the constituent entities of the Russian Federation and the attraction of extrabudgetary sources. Further opportunities for the development of domestic and inbound tourism based on structural market changes that began in 2014 are outlined. The principles for the development of a tourism development strategy for the long-term period are formulated.